Perencanaan Manajemen Strategik Dalam Meningkatkan Mutu Pendidikan di Sekolah SD Negeri 115509 Simpang Marbau - Inom Nasution; Khadijah Pasaribu; Rahmiatul Zuhro; Bunga Br Lubis; Tengku Lailan Khairuni; Lailatul Purba; Okta Manurung; Mely Suryani Siregar (Peneliti.net, 2022)
This study was conducted to see how strategic management planning is carried out by teachers in improving the quality of education in schools. whether in this strategic management planning there is an increase in the quality of education or not. Therefore, we want to interview one or several teachers to get data or results from what they feel while in school at this time whether the planning has improved the quality of education effectively or there is no improvement in the quality of education. And this time we will see it in the research we will do at the 115509 Simpang Marbau Elementary School.